2022
DOI: 10.3389/fmicb.2022.987056
|View full text |Cite
|
Sign up to set email alerts
|

A super absorbent polymer containing copper to control Plenodomus tracheiphilus the causative agent of mal secco disease of lemon

Abstract: The aim of this study was to determine the effectiveness of a Super absorbent polymer (SAP) containing copper (SAP-Cu) in controlling mal secco disease (MSD) of lemon caused by the fungus Plenodomus tracheiphilus. Super absorbent polymer containing copper was characterized by atomic absorption spectrometry (AAS) and UV-VIS spectroscopy. In vitro tests were performed to determine the inhibitory effects of SAP-Cu against the pathogen on both potato-dextrose-agar medium and naturally infected lemon cuttings. Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…In recent decades, new formulations have been exploited in agriculture for several purposes, including the application of plant-beneficial organisms, improving water use efficiency, enhancing seed germination, or delivering agrochemicals such as fertilizers or fungicides [ 30 , 31 ]. Bacterial strains in the present study have been reported as promising PGPR in studies of cells in a liquid formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, new formulations have been exploited in agriculture for several purposes, including the application of plant-beneficial organisms, improving water use efficiency, enhancing seed germination, or delivering agrochemicals such as fertilizers or fungicides [ 30 , 31 ]. Bacterial strains in the present study have been reported as promising PGPR in studies of cells in a liquid formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Those isolates were sourced from the collection of the Molecular Plant Pathology laboratory of the Department of Agriculture, Food and Environment, Catania University, Italy, the Colección Española de Cultivos Tipo (CECT), Valencia University, Spain, and ITEM Collection from Istituto di Scienze delle Produzioni Alimentari (ISPA), National Research Council, Bari, Italy. Most of them were characterized in previous studies (El boumlasy et al, 2022; La Spada et al, 2021; Carlos Luz et al, 2021; Migheli et al, 2009; Riolo et al, 2020, 2021, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the antifungal activity of isolates, LABs were tested in vitro against pathogenic fungi s.l., i.e. Most of them were characterized in previous studies (El boumlasy et al, 2022;La Spada et al, 2021;Carlos Luz et al, 2021;Migheli et al, 2009;Riolo et al, 2020Riolo et al, , 2021Riolo et al, , 2022.…”
Section: Bacterial and Fungal Strainsmentioning
confidence: 99%
“…Spraying with authorized copper-based fungicides are also carried out, especially on young plants from nurseries (Abbate et al 2019). However, these treatments are causing concerns related to the long-lasting persistence of copper in the environment with the consequent toxic effects toward plants, animals and soil microbiota, and related to the contamination of food (Abbate et al 2019;El Boumlasy et al 2022). In this respect, a new promising super absorbent polymer (SAP) has been shown to act as an efficient reservoir for the controlled release of copper, specifically in the treatment of pruning cuts of lemon twigs affected by the Mal Secco.…”
Section: Mal Secco Caused By Plenodomus Tracheiphilusmentioning
confidence: 99%